P15-T Increased HCN4 expression in hippocampus of SUDEP patients. Issue 7 (July 2019) - Papanicolou, Maria; Butt, Arthur; Moore, Christopher
Abstract : Background: Sudden Unexpected Death in Epilepsy (SUDEP) accounts for approximately 17% of epilepsy related deaths though the pathophysiological mechanisms remain poorly understood. Seizure related cardiac and respiratory dysfunction if often seen as the terminal event with sodium and potassium cardiac channelopathies causing a long QT syndrome. More recently the hyperpolarization-activated cyclic nucleotide–gated (HCN) channels have been shown to be involved in animal models of epilepsy and abnormal genotypes seen in some patients. Here we report the first studies of HCN expression in tissue form human SUDEP patients. Methods: Anonymous donor human brain tissue from patients aged 19–31 years and normal controls was obtained from Oxford Brain Bank, UK. Standardised Immunohistochemistry was performed using primary antibodies against HCN1-4 subunits. Cells expressing the HCN were counted using Volocity Software (Perkin Elmer). All results were expressed as a mean (±SEM). Results: Immunoreactivity for HCN channels was detected principally in pyramidal neurons of the CA1 area and in the dentate gyrus (DG) of the hippocampus. The only observed difference was a significant increase in HCN4 expression in the DG of SUDEP tissue. (231 ± 41 vs. 111 ± 10, p = 0.044). Discussion: HCN4 has been implicated in patients with cardiac dysfunction and one HCN4 gene abnormality linked directly to SUDEP. We are unable to tell whether this upregulation represents a primary cause of the epilepsy of a secondary bystander phenomenon that has led to sudden death but feel that the role of HCN channel regulation in epilepsy and SUDEP has yet to be fully understood.